Pengaruh Fee Audit, Time Budgeting, dan Rotasi Audit Terhadap Kualitas Audit dengan Ukuran Perusahaan sebagai Variabel Moderasi - Dwiane Harya Rahadi; Abriandi (UNIVERSITAS KALBIS, 2022)
This research was aim to know the influences audit fees, time budgeting, and audit switching of audit quality with company size as a moderation variable. This research uses quantitative methods through secondary data in the form of annual financial reports and participants. The population used in this research is in the infrastructure, utilities and transportation sectors listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique is a purposive sampling method that produces a sample of 25 companies with observations for 5 years. The results of this research indicate that audit fees, time budgeting, and audit switching partially cannot influence improving the quality of audit results, nor with firm size being able to moderate the effect of audit fees, time budgeting, and audit switching on audit quality. This means because, company size is basically only a condition of company size, which is not possible to be influenced by the professionalism of the auditor.